Pengaruh Faktor Predisposisi, Pendukung, dan Penguat terhadap Pemberian Imunisasi HB-0 di Wilayah Kerja Puskesmas Bandar Baru Kecamatan Sibolangit Tahun 2025 - Dessy Meilani Hutasoit (JURNAL RISET RUMPUN ILMU KESEHATAN, 2024)
HB 0 immunization in Bandar Baru Health Center, Sibolangit District is still low at 39.0%. The low HB 0 immunization in infants is related to predisposing factors such as knowledge and attitudes, supporting factors, namely the place of delivery and reinforcing factors that support the family. This study aims to analyze predisposing, supporting and reinforcing factors related to the provision of HB 0 immunization in the Bandar Baru Health Center area, Sibolangit District. This type of research is a survey using an explanatory research approach. The population in this study were all mothers who had babies at the Bandar Baru Health Center, Sibolangit District, as many as 68 people and a sample of 68 people. Data were obtained by means of interview questionnaires and observations, analyzed using Multiple Logistic Regression statistical tests at = 5%. The results of the study showed that there were significant predisposing factors such as knowledge and attitudes, supporting factors were the place of delivery, reinforcing factors were family support for HB 0 immunization in the Bandar Baru Health Center area, Sibolangit District and the variable that most influenced HB 0 immunization in the Bandar Baru Health Center, Sibolangit District where the workforce was a variable with Exp B = 12,733. It is possible for health workers to provide socialization to mothers about HB 0 immunization to increase HB 0 immunization, the Deli Serdang Regency Health Office should further improve implementation and provide education to the community about the HB 0 program and the community at the Bandar Baru Health Center, Sibolangit District must carry out hepatitis B prevention.